Greenhouse Selection for Drought Resistance in Rice - O'Toole, J.C.; Maguling, M.A. (Wiley, 1981)
The protocol used in greenhouse drought resistance screening of rice, including monitoring of soil and plant water status, is described. Monitoring of dawn leaf water potential and subsequent visual scoring for drought resistance of 2,074 entries suggests that ability to maintain relatively high leaf water potential is strongly influencing selection by current visual scoring techniques. Cultivars receiving desirable scores are mainly dryland adapted rices from West Africa, Brazil, and some South and Southeast Asian hill rices.